2020
DOI: 10.1111/asj.13361
|View full text |Cite
|
Sign up to set email alerts
|

The anti–heat stress effects of Chinese herbal medicine prescriptions and rumen‐protected γ‐aminobutyric acid on growth performance, apparent nutrient digestibility, and health status in beef cattle

Abstract: The high temperature and humid weathers coupled with low wind speed can induce heat stress in animal, resulting in reduced growth performance, compromised health status, or even death (Mader, Davis, & Brown-Brandl, 2006). Heat stress is known to disturb metabolic and physiological processes required for optimal cattle productivity, as well as cattle immunity (Collier, Collier, Rhoads, & Baumgard, 2008; Rhoads et al., 2009; West, 2003). Previous studies demonstrated that heat stress lowers average daily feed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…This suggested that fermented HTR could alleviate heat stress symptoms of fattening cattle in summer, which is consistent with the results of other studies [36-38]. Chen found that Chinese herbal medicine could reduce signi cantly the RR of beef cattle under heat stress [37]. Song found that Chinese herbal medicine could reduce the RT for a certain period of time under high temperature [36].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This suggested that fermented HTR could alleviate heat stress symptoms of fattening cattle in summer, which is consistent with the results of other studies [36-38]. Chen found that Chinese herbal medicine could reduce signi cantly the RR of beef cattle under heat stress [37]. Song found that Chinese herbal medicine could reduce the RT for a certain period of time under high temperature [36].…”
Section: Discussionsupporting
confidence: 87%
“…Our ndings showed that the thyroid function of beef cattle decreased and the amount of T4 secreted by the thyroid gland decreased, thus reducing heat production and improving the body's adaptability to the thermal environment. Chen and other researchers applied Chinese herbal medicine to heat stressed beef cattle, and also found that the level of T4 decreased, demonstrating that Chinese herbal medicine can alleviate the heat stress of beef cattle [37].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This suggested that fermented HTR could alleviate heat stress symptoms of fattening cattle in summer, which is consistent with the results of other studies [ 35 37 ]. Chen found that Chinese herbal medicine could reduce significantly the RR of beef cattle under heat stress [ 36 ]. Song found that Chinese herbal medicine could reduce the RT for a certain period of time under high temperature [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Body temperature must be kept within physiological limits of the animal to stay healthy and productive. High ambient temperatures along with low wind speeds can cause heat stress in animals, resulting in decreased growth, poor health, or even death (Chen et al, 2020). As a result, animals must adapt to their surroundings in order to produce more and better.…”
Section: Introductionmentioning
confidence: 99%